(untitled) (Movimenta (ISSN 1984-4298), 2022)
Introduction: Neurological and movement assessment may show early brain alteration or immaturity. Objective: Compare the neurological assessment and general movements of at-risk babies with 40 and 52 weeks of life in a public hospital that is a reference in the maternal-infant area. Methods: Longitudinal, prospective study, 15 babies at risk admitted to an Intermediate Unit of a public hospital. The Hammersmith Neonatal Neurological Examination (HNNE) scale was used at 40 weeks and the Hammersmith Infant Neurological Examination (HINE) at 52. The General Movements Assessment (GMA) evaluated general movements, as well as the presence or absence of “Fidgety. To compare means, the t-student test was applied; Mann-Whitney in asymmetries; Fisher’s exact test in proportion comparisons; Spearman correlation in the associations. The significance level was 5% (p≤0.05) and the analyzes were performed using SPSS*/28.0. Results: Boys (80%), whites (66.7%) and cesarean delivery predominated. Means and medians were: Apgar nine, six prenatal visits, gestational age (GA) of 36.8 weeks. The “altered assessment” predominated in the HNNE and HINE (p=1.000); GMA, the “normal assessment” and presence of Fidgety. Altered HNNE/HINE appeared in older and heavier babies, GMA for younger and lighter babies. HINE was positively associated with GMs, both “altered assessment”, and association of “normal assessment” of GMA and HINE (p= 0.044). Conclusion: At-risk babies had a similar assessment over time. Babies with a higher GI showed alterations in the neurological assessment and those with a lower GA in the GMA. Both scales must be performed as one complement of the other. er.